China Blue - Peled, Micha X. (United States : Teddy Bear Films Inc., 2005)
China Blue is a powerful and poignant journey into the harsh world of sweatshop workers. Shot clandestinely, this is a deep-access account of what both China and the international retailers don't want us to see: how the clothes we buy are actually made. Following a pair of denim jeans from birth to sale, China Blue links the power of the U.S. consumer market to the daily lives of a Chinese factory owner and two teenaged female factory workers. Filmed both in the factory and in the workers' faraway village, this documentary provides a rare, human glimpse at China's rapid transformation into a free market society.
Keywords: Documentary films